Peer support service activity prevalence by setting: a nine-state survey of peer workers - Hagaman, Angela; Warren, Hannah L.; Miller, Ruth; Henderson, Craig (Frontiers in Public Health, 2025)
IntroductionPeer recovery support services (PRSS) are flexible, evidence-informed interventions that can be provided in a variety of settings and are delivered by credentialed people with lived-experience of mental health and substance use disorders. PRSS are a promising intervention that may increase linkage to care, treatment retention, and long-term recovery; however, there remains a sizable gap in the literature to disseminate these services to scale. Misunderstanding of the peer worker role, and a lack of consistent nomenclature to describe PRSS activities are barriers to studying PRSS effectiveness.MethodsThis sequential exploratory mixed-methods study began with a qualitative and methodological review of a previous peer worker survey instrument by eight subject matter experts with lived experience of substance use disorder. The improved 38-item web-based survey was then disseminated to a non-probability sample of peer workers in nine U.S. states.ResultsA total of 659 peer workers responded to the survey indicating that they perform an average of 24 different service activities most of the time (M = 23.6; SD = 16.7). PRSS interventions were most commonly delivered in communities and neighborhoods, client homes, and recovery community organizations. Survey participants reported spending approximately half of their time (M = 43.1, SD = 26.1) providing Emotional support, and less than one quarter of their time providing Affiliational (M = 21.3%; SD = 18.5), Informational (M = 18.0%; SD = 15.5), and Instrumental (M = 15.0%; SD = 15.3) support.DiscussionThis study may be the first of its kind to explore the broad array of service activities peer workers perform in multiple settings across regional service networks, also known as recovery ecosystems. Notably, peer worker respondents selected an average of 24 activities that they perform most of the time, and Emotional support was the most commonly delivered support type. Study results provide preliminary evidence about where PRSS are performed within both macro and micro settings indicating that services are frequently delivered in non-clinical community-based settings and client homes which may confer added benefit. These results can be used to inform future studies that examine the effectiveness of PRSS across the continuum of care.